The Cheshire Cheese cat : a Dickens of a tale - Deedy, Carmen Agra; Wright, Randall (Peachtree, 2014)
A community of mice and a cheese-loving cat form an unlikely alliance at London's Cheshire Cheese, an inn where Charles Dickens finds inspiration and Queen Victoria makes an unexpected appearance.